Limited Functional Effects of Subacute Syngeneic Bone Marrow Stromal Cell Transplantation after Rat Spinal Cord Contusion Injury. Issue 1 (January 2016) - Sandner, Beatrice; Ciatipis, Mareva; Motsch, Melanie; Soljanik, Irina; Weidner, Norbert; Blesch, Armin
Cell transplantation might be one means to improve motor, sensory, or autonomic recovery after traumatic spinal cord injury (SCI). Among the different cell types evaluated to date, bone marrow stromal cells (BMSCs) have received considerable interest due to their potential neuroprotective properties. However, uncertainty exists whether the efficacy of BMSCs after intraspinal transplantation justifies an invasive procedure. In the present study, we analyzed the effect of syngeneic BMSC transplantation following a moderate to severe rat spinal cord injury. Adult Fischer 344 rats underwent a T9 contusion injury (200 kDy) followed by grafting of GFP-expressing BMSCs 3 days postinjury. Animals receiving a contusion injury without cellular grafts or an injury followed by grafts of syngeneic GFP-expressing fibroblasts served as control. Eight weeks post-transplantation, BMSC-grafted animals showed only a minor effect in one measure of sensorimotor recovery, no significant differences in tissue sparing, and no changes in the recovery of bladder function compared to both control groups in urodynamic measurements. Both cell types survived in the lesion site with fibroblasts displaying a larger graft volume. Thus, contrary to some reports using allogeneic or xenogeneic transplants, subacute intraparenchymal grafting of syngeneic BMSCs has only a minor effect on functional recovery.